PENGARUH SUPLEMEN IODIUM DAN BETA KAROTEN TERHADAP STATUS IODIUM DAN STATUS GIZI IBU HAMIL DI DAERAH ENDEMIK GAKI - Astuti Lamid; Rimbawan Rimbawan; Ali Khomsan; Clara Meliyanti Kusharto; Muhilal Muhilal (Media Gizi dan Keluarga, 2007)
ABSTRACT. Iodine Deficiency Disorders (IDD) prevalence ofpregnant women is 16% and this would have consequence of risk during delivery and  nutritional status of the children. The aims ofthis study was to measure the effect ofiodized oil and beta carotene on the nutritional, iodine and thyroid stimulating hormone (TSH) status of pregnant women and to determine nutrition, iodine and cyanide intakes from food consumed by pregnant women. Research design ofthe study was quasi experiment. Pregnant women on the first trimester were chosen and divided into three groups. The first group was given iodized oil at 200mg iodine, the second group was treated with iodized oil at 30mg iodine every month for 6 months, and the third group was given as group 2 plus beta-carotene at 30mg each month for six months. Data collected were nutrients, iodine, and cyanide intake from food consumed and the parameter measured were serum TSH, urine iodine excretion (UIE), body weight and upper arm circumference. Chi Square, ANOVA and Kruskall Wallis were applied for statistical analysis. Iodine consumed by pregnant women was closed to the recommended daily allowance (RDA). iodized oil supplement could increase the UIE for 2 times at trimester 3 ofthe pregnancy. Furthermore, the treatment could redure the TSH value during pregnancy. The supplement could supply iodine during pregnancy. Keywords: iodine, hipothyroid, beta caroten, nutritional status